Modelling of serrated chip formation processes using the stabilized optimal transportation meshfree method - Huang, Dengpeng; Weißenfels, Christian; Wriggers, Peter (International Journal of Mechanical Sciences, 2019)
Numerical modelling of chip formation is important for a better understanding thus for an improvement of the high speed metal cutting process. The challenge in the modelling of chip formation lies in capturing the shear band formation, the material separation and the tool-chip interaction accurately. Mostly, some assumptions are made when modelling the material separation and the serrated morphology generation, which leads to an unrealistic prediction of the chip formation. In this work, both the serrated morphology on the chip upper surface and the material separation at the chip root are treated using a ductile fracture model. Additionally, a recently developed Galerkin type meshfree scheme, the stabilizedoptimal transportation meshfree (OTM) method is applied as a numerical solution method in combination with a material point erosion approach. This enables the modelling of material separation and serrated morphology generation of the cutting process in a more realistical and convenient way. The frictional contact force exerted by the cutting tool is imposed on the workpiece using a predictor-corrector strategy. The shear band formation is described by the thermal softening term in the Johnson-Cook plastic flow stress model. Using this model, it can be demonstrated that thermal softening is the main cause for the shear band formation. However, this phenomenon is under-predicted by the Johnson-Cook flow stress model. Additionally, it can be seen that the Johnson-Cook fracture model shows limitations in capturing the fracture on the chip upper surface. Thus, a supplementary condition for the stress triaxiality is applied. This condition allows a more accurate measurement of the chip size, like chip spacing, peak and valley. These improvements are demonstrated by comparing the calculated chip morphology, cutting force and chip formation procecs with experimental results.
Keywords: High speed machining; Serrated chip formation; Ductile fracture; Stabilized OTM